Effects of dietary lipid sources on flavour volatile compounds of brown trout (Salmo trutta L.) fillet - Giovanni Turchini; T Mentasti; F Caprino; S Panseri; V Moretti; F Valfre (2004)
The high cost and unpredictable availability of fish meal and fish oil (FO) forced feed mill companies to look for alternative ingredients for aquafeeds. In this study, the effects of alternative dietary lipid sources [FO as control, canola oil (CO), oleine oil (OO), poultry fat (PF) and pork lard (PL)] in trout feed on flavour volatile compounds occurring in brown trout (Salmo trutta L.) fillet were evaluated after 70 days of feeding (rearing temperature 14.6°C). Total amounts of volatile compounds identified were higher for fillets of fish fed diets containing only FO as lipid sources. Total amount of alcohols and aldehydes of the fillets were linearly directly related to the percentage content of polyunsaturated fatty acids (PUFA) n-3 of brown trout flesh. The use of alternative dietary lipid sources, modifying the fillet fatty acids composition, affect the total amount of volatile compounds and, changing the relative amount of each volatile compound, affect the flavour of the fish flesh.